Different Approaches to the Modelling of COVID-19 - Meyer, J. F. C. A.; Lima, M.; Espitia, C. C.; Longo, F.; Laiate, B.; Gois, A. N.; Kunz, C. F. D. (Trends in Computational and Applied Mathematics, 2021)
In this paper some innovative aspects of the mathematical modelling of classic epidemiology problems for the study of models related to the COVID-19 pandemic dynamics are presented. In addition, they are compared to real-world data using numerical methods in order to approximate the solutions. One of these models includes a non-transmitting compartment and another one, a delay-differential equation in the SIR-type method. Finally, a comparative discussion of the results is also presented.